2010
DOI: 10.1002/casp.1074
|View full text |Cite
|
Sign up to set email alerts
|

Police responses to diversity: A social representational study of rural British policing in a changing representational context

Abstract: In the first decade of the 21st century, British policing faced two new challenges in how it responded to social diversity: As well as instituting reforms in response to a highly publicized report describing the British police as 'institutionally racist' (Macpherson, 1999), they faced challenges associated with rapid increases in numbers of immigrants into the UK. Studying social representations at such times of change allows access into processes, themes and value systems that may otherwise remain hidden. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In much of the previous research, there is an implicit point of departure that takes diversity and categories such as gender, ethnicity and sexuality to be fixed and pre-determinate as concepts. In contrast, and in line with a growing body of other research, this article directs its analysis to the processes through which these concepts are constructed, maintained, and legitimised in the police force (Holdaway 1997, Frewin and Tuffin 1998, McElhinny 2001, Dick and Cassell 2002, Holdaway and O'Neill 2007a, 2007b, Loftus 2008, Boogaard and Roggeband 2010, Morant and Edwards 2011, Morash and Haarr 2012, Lander 2013, Hansen Löfstrand and Uhnoo 2014, Rennstam and Sullivan 2018. Focusing on the processes of legitimisation renders visible how exclusionary practices are reproduced within the police, helping to find an answer to the question of how exclusionary practices based on ethnic boundaries are reproduced in a discursive climate in which diversity is officially affirmed as a guiding principle (e.g.…”
Section: Theory and Methodology: The Why And How Of Discourse Analysis In Police Researchmentioning
confidence: 92%
See 2 more Smart Citations
“…In much of the previous research, there is an implicit point of departure that takes diversity and categories such as gender, ethnicity and sexuality to be fixed and pre-determinate as concepts. In contrast, and in line with a growing body of other research, this article directs its analysis to the processes through which these concepts are constructed, maintained, and legitimised in the police force (Holdaway 1997, Frewin and Tuffin 1998, McElhinny 2001, Dick and Cassell 2002, Holdaway and O'Neill 2007a, 2007b, Loftus 2008, Boogaard and Roggeband 2010, Morant and Edwards 2011, Morash and Haarr 2012, Lander 2013, Hansen Löfstrand and Uhnoo 2014, Rennstam and Sullivan 2018. Focusing on the processes of legitimisation renders visible how exclusionary practices are reproduced within the police, helping to find an answer to the question of how exclusionary practices based on ethnic boundaries are reproduced in a discursive climate in which diversity is officially affirmed as a guiding principle (e.g.…”
Section: Theory and Methodology: The Why And How Of Discourse Analysis In Police Researchmentioning
confidence: 92%
“…Focusing on the processes of legitimisation renders visible how exclusionary practices are reproduced within the police, helping to find an answer to the question of how exclusionary practices based on ethnic boundaries are reproduced in a discursive climate in which diversity is officially affirmed as a guiding principle (e.g. Shearing and Ericson 1991, McElhinny 2001, Loftus 2009, Morant and Edwards 2011, Souhami 2014, Uhnoo 2015. Thus, this article looks at how police recruits' talk constructs diversity in relation to the police force and to police work.…”
Section: Theory and Methodology: The Why And How Of Discourse Analysis In Police Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these differences, both rural and metropolitan officers agreed that the seriousness of the offense and harm caused by the offense were the most important predictors of behavior, while race and gender were the least important (Schulenberg, 2010). In contrast, other scholars have found that rural officers describe handling interactions with minorities differently than whites when recalling past interactions to researchers (Morant and Edwards, 2011).…”
Section: Rural Policing In Americamentioning
confidence: 89%
“…."). Such dialogism within a conversational turn is evident when police defend themselves against accusations of racism (Morant & Edwards, 2011) and in argumentative positioning around immigration (Gillespie et al, 2012;Tsirogianni & Andreouli, 2011). People use semantic barriers, such as dichotomies, taboos, and stigma, to neutralize threatening meanings (Gillespie, 2008;Moscovici, 1976).…”
Section: Defensive Tacticsmentioning
confidence: 99%